Ta’lim al-Lughah al-‘Arabiyah wa Thariqah Tathbiqiha fi Ta’lim al-Sharf ‘Ala Asasi al-Nadzariyah al-Bunyawiyah - Hamdy, Mohammad Zainal; Afyuddin, Moh. Sholeh; Maesaroh, Miftahul (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
The view of structuralism is Language learning is the acquisition of habits that are strengthened by practice and reinforcement. Language is a skill that is obtained from the surrounding environment and then carried out through imitation and reinforcement methods. Among the Arabic language approaches is a structural approach which requires students to understand language formulas and terms, and students are required to memorize sentence models or word functions. In Arabic, we can see that learning with a structural approach is required to know fi'il, fa'il, maf'ul and many other linguistic terms. researchers use qualitative research and types of literature review or library research is an activity of studying reference books. This activity is useful for obtaining a theoretical basis related to the problem under study. Literature study is the activity of reading books and looking for references. The goal is for researchers to understand a topic or research theme. The structural theories are one of the other theories in the research of modern linguistics. He defined language as the spoken one, and that its acquisition by adding exercises, reinforcement, and so on is one of the most important principles in this theory. Hence, we knew that the structural theory had tried to focus the teaching of the language on the teaching of the spoken language, and by basing the teaching of grammar on it, it was hoped that the teaching of grammar seemed effective and important in the hearts of students.